Correlations between Different Heavy Metals in Diverse Body Fluids: Studies of Human Semen Quality - Lidia Mínguez-Alarcón; Jaime Mendiola; Manuela Roca; José J. López-Espín; José J. Guillén; José M. Moreno; Stella Moreno-Grau; María J. Martínez-García; Nuria Vergara-Juárez; Belén Elvira-Rendueles; Antonio García-Sánchez; Jorge Ten; et al. (Advances in Urology)
It has been hypothesized that exposure to heavy metals may impair male reproduction. To measure the effect produced by low doses of heavy metals on semen parameters, it is necessary to clarify in which body fluids those measurements must be performed. Sixty-one men attending infertility clinics participated in our study. Concentrations of lead, cadmium, and mercury were measured in whole blood, blood plasma, and seminal plasma using spectroanalytical and electrochemical methods. Semen analyses were performed according to World Health Organization criteria. For statistical analysis, Spearman's rank correlations, mean comparison tests, and discriminant analysis were calculated. Significant correlations between the measured concentrations of the three heavy metals in the same biological fluids were observed. However, no similar relationship was seen when comparing the concentrations in different body fluids of the same metal. According to our results and previous publications, seminal plasma might be the best body fluid for assessing impairment of human semen parameters.